Analysis Of Multiply-Connected Acoustic Filters with Application To Design Of Combination Mufflers And Underwater Noise Control Linings - Panigrahi, Satyanarayan (2008)
This thesis endeavors towards developing various concepts employed in analysis and design of acoustic ﬁlters for varied applications ranging from combination mufflers for automobiles to complex networks of gas carrying ducts to multiply connected complex automotive silencing devices to the noise control coatings for underwater applications.